IMPROVING THE METHODOLOGICAL BASIS OF ACCOUNTING FOR FINANCIAL ASSETS - Kholmirzaev Ulugbek Abdulazizov; Ibrogimov Sherzod; Sabaydullaeva Markhabat Abdulkhodinevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In our national accounting system, financial assets are a comprehensive and unexplored object. This is also true of the methodological aspects of the issue. In the course of the study, we considered, as far as possible, the most important foundations on which the methods of accounting and analysis of financial assets are developed and maintained in order to know and improve their methods. In our opinion, a method is a set of methods and rules for the purposeful performance of accounting and analytical work. There are general and specific methods in accounting and analysis. The conceptual framework of financial accounting and reporting is an important fundamental structure on which general and specific methods are based. Hence, the more thoroughly this fundamental structure is developed, the more reliable and acceptable the methods derived from it will be.